Applying an internal transcribed spacer as a single molecular marker to differentiate between Tetraselmis and Chlorella species - Fathy, Wael A.; Techen, Natascha; Elsayed, Khaled N. M.; Essawy, Ehab A.; Tawfik, Eman; Alwutayd, Khairiah Mubarak; Abdelhameed, Mohamed S.; Hammouda, Ola; Ross, Samir A. (Frontiers in Microbiology, 2023)
In the realm of applied phycology, algal physiology, and biochemistry publications, the absence of proper identification and documentation of microalgae is a common concern. This poses a significant challenge for non-specialists who struggle to identify numerous eukaryotic microalgae. However, a promising solution lies in employing an appropriate DNA barcoding technique and establishing comprehensive databases of reference sequences. To address this issue, we conducted a study focusing on the molecular characterization and strain identification of Tetraselmis and Chlorella species, utilizing the internal transcribed spacer (ITS) barcode approach. By analyzing the full nuclear ITS region through the Sanger sequencing approach, we obtained ITS barcodes that were subsequently compared with other ITS sequences of various Tetraselmis and Chlorella species. To ensure the reliability of our identification procedure, we conducted a meticulous comparison of the DNA alignment, constructed a phylogenetic tree, and determined the percentage of identical nucleotides. The findings of our study reveal the significant value of the ITS genomic region as a tool for distinguishing and identifying morphologically similar chlorophyta. Moreover, our results demonstrate that both the ITS1 and ITS2 regions are capable of effectively discriminating isolates from one another; however, ITS2 is preferred due to its greater intraspecific variation. These results underscore the indispensability of employing ITS barcoding in microalgae identification, highlighting the limitations of relying solely on morphological characterization.